Cannabis Legalization in Canada: Reflections on Public Health and the Governance of Legal Psychoactive Substances - Crépault, Jean-François (Frontiers in Public Health, 2018)
The Canadian government is “taking a public health approach to legalizing, strictly regulating and restricting access to cannabis.” There is, however, no universally accepted definition of a public health approach to cannabis. This paper presents what such an approach is, and is not, and discusses its applicability to legal psychoactive substances more generally. It critically reflects on the role of the public health sector in the governance of addictive substances and activities, noting its function of "responsibilizing" individuals and coaxing them to self-regulate - and the contradiction involved when other state actors involved in governance are actively inciting consumption of those substances and activities.